P-043 Stenting for pseudotumor: angiographic and hemodynamic follow-up and patterns of hemodynamic failure. (4th July 2012) - Kumpe, D; Seinfeld, J; Ho, J; Mei, Q; Zhang, Y
Abstract : Introduction/purpose: Stenting of a dural sinus for idiopathic intracranial hypertension (IIH) (pseudotumor cerebri), is becoming recognized as a potential cure for the subgroup of patients who have venous outflow obstruction. The reported number of stenting cases in the world literature more than tripled in the last half of 2011, when another 103 cases were added to the previously reported 42 cases. New stenosis formation in the transverse sinus (TS) above the stent has been mentioned casually in the literature, without any angiographic images showing this pattern of recurrence. The only report of this phenomenon in a case series was in 6/52 patients (12%) (Ahmed RM, Wilkinson M, et al. AJNR 2011;32 :1408–14). They reported clinically successful outcomes after restenting in all six patients, five with a single restenting and one with three restentings. The latter case is the only report of failure after repeat stenting, without details or images. These authors theorized that the collapsed transverse sinus was a "Starling resistor" (resistance is dependent on ambient pressure) and that stenting of the TS would reverse pseudotumor pathophysiology even if the primary problem is not venous outflow obstruction. They suggested that stenting of the entire transverse sinus might prevent hemodynamic failure. We will present our current results, with previously unreported follow-up angiographic images and hemodynamic documentation of patients who have developed further stenoses and recurrent elevated pressure gradients after restenting. Materials and Methods: At present we have angiographic and hemodynamic follow-up on 18 of 22 patients in whom we have performed unilateral dural sinus stenting. These 18 patients included 6 males and 4 females who were "atypical" (BMI ≤25 in two teen agers, 16 and 17-year old, and two female patients in their 50s. There were eight "typical" pseudotumor patients (overweight females of childbearing age). Results: Five patients developed recurrence of the pressure gradient between the superior sagittal sinus and the internal jugular vein, with development of a new stenosis in the TS above the stent, and a recurrent pressure gradient across the new stenosis. We restented the newly stenosed TS segment in three patients. Two of the three then redeveloped new stenoses in the torcular/superior sagittal sinus region above the second stent, as well as new stenoses in the contralateral TS, with a second recurrence of the pressure gradient. One of our hemodynamic failures occurred in a patient in whom the entire TS was stented. This patient has not been restented. While this hemodynamic failure phenomenon has occurred in 28% (5/18) of our patients overall, all five have occurred in females, and four have occurred in the eight patients who are "typical" IIH patients (50% of "typical" patients). Conclusions: Stenting of the entire transverse sinus does not universally prevent restenosis above the stent. Restenting in new TS stenosis above the first stent did not prevent further hemodynamic failure. New stenoses above the second stent developed in 2 of 3 patients. "Typical" IIH patients may have a higher incidence of hemodynamic failure than "atypical" patients. Competing interests: D Kumpe: royalties, Cook Inc. J Seinfeld: None. J Ho: None. Q Mei: None. Y Zhang: None.